The real effect of the initial enforcement of insider trading laws - Chen, Zhihong; Huang, Yuan; Kusnadi, Yuanto; John Wei, K.C. (Journal of Corporate Finance, 2017)
Based on a difference-in-differences approach, we find strong evidence that the initial enforcement of insider trading laws improves capital allocation efficiency. The effect is concentrated in developed markets and manifests shortly after the enforcement year. Further analysis shows that the improvement is positively associated with the increase in liquidity around the enforcement year and the opaqueness of the information environment before the enforcement year. The improvement is more pronounced for firms operating in more competitive markets, being more financially constrained, and with more severe agency problems. Finally, we find increased accounting performance after the enforcement and the increase is positively associated with the improvement in capital allocation efficiency. Overall, our evidence suggests that the initial enforcement of insider trading laws improves capital allocation efficiency by providing more information to guide managerial decisions and by reducing market frictions arising from information asymmetry and agency problems.